IEEE standard dictionary of electrical and electronics terms - Institute of Electrical and Electronics Engineers; Jay, Frank; Institute of Electrical and Electronics Engineers (New York: Institute of Electrical and Electronics Engineers, 1977)
The 1972 edition of the IEEE Standard Dictionary of Electrical and Electronics Terms included all terms and definitions that had been standardized previously by IEEE, as well as many American National Standards and IEC terms. The current edition derives the bulk of its new definitions from standards published between 1968 and 1977. Most of the definitions that have been continued from the 1972 edition have been reaffirmed because of their inherent usefulness.
Edition for 1972 by the Dictionary Subcommittee of the Institute of Electrical and Electronics Engineers.
ne 10/05/2018
Loans
Keywords: Electrical engineering; Electronics